Analysis of tungsten spectral-lines recorded from laser-target experiment - Tsarenko, A.V.; Marchenko, A.K.; Sadowski, M.J.; Skladnik-Sadowska, E.; Malinowski, K.; Wolowski, J.; Czarnecka, A.; Gąsior, P.; Parys, P.; RosiĔski, M. (Вопросы атомной науки и техники, 2006)
The paper is devoted to an analysis of selected experimental results obtained from space- and time-resolved spectroscopic
measurements, which were performed during the interaction of an intense laser-beam (0.7 J, 2 ns) with a tungsten (W) target placed
under high-vacuum conditions. The spectroscopic measurements were carried out by means of a Mechelle®
900 optical-spectrometer,
and for the first time some tungsten spectral lines (WI and WII) were recorded. The most important parameters of a tungsten plasma
plume were estimated using the fitting procedure. The appearance of the tungsten ions was also confirmed by a series of corpuscular
measurements